Method for preparing artificial rutile by intensified acid leaching of ilmenite concentrate

By applying pulsed magnetic field in the ilmenite concentrate acid leaching process, the problems of high impurity content and low concentration acid leaching efficiency in the existing process are solved, and the efficient leaching of ilmenite concentrate in low concentration acid solution and the preparation of high-grade artificial rutile is achieved.

CN119753365APending Publication Date: 2025-04-04ZHENGZHOU UNIV +1

Patent Information

Application Number
CN202410611165.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The titanium-rich material obtained by the existing process for preparing titanium-rich material has a high impurity content, and low-concentration acid leaching cannot achieve high-efficiency leaching effect.

Method used

The ilmenite concentrate strengthens acid leaching method is adopted to add a pulsed magnetic field during the acid leaching process, and the magnetic field is used to activate the magnetic minerals of ilmenite concentrate, thereby improving its solubility and leaching efficiency in low-concentration acid solutions.

Benefits of technology

The efficient leaching of ilmenite concentrate in low-concentration acid solution is achieved, production efficiency is improved, high-grade artificial rutile is obtained, and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753365A_ABST
    Figure CN119753365A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-quality artificial rutile through strengthened acid leaching of ilmenite concentrate, and belongs to the technical field of metallurgy. The method is used for solving the problems that a titanium-rich material obtained by an existing titanium-rich material preparation process is high in impurity content; and low-concentration acid leaching cannot achieve an efficient leaching effect. According to the method, a magnetic field is added in the acid leaching process. By means of the method, efficient leaching of titanium and iron elements under the low-concentration acid condition can be achieved, and the obtained artificial rutile is high in grade, high in efficiency and good in leaching effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgical technology and specifically relates to a method for preparing high-quality artificial rutile by enhanced acid leaching of ilmenite concentrate. Background Art

[0002] The efficient production of titanium dioxide and titanium sponge is an important support for the development of the titanium industry. my country has abundant titanium resources, mainly ilmenite rock. Among them, ilmenite in Panzhihua, Sichuan, Chaoyang, Liaoning, Chengde, Hebei and other regions is an important titanium resource. This kind of ilmenite concentrate has low titanium grade and high impurity content, which cannot meet the requirements of the chloride titanium dioxide and titanium sponge production process for raw materials. Most of them are smelted and extracted by sulfuric acid method.

[0003] Compared with the sulfuric acid process for titanium dioxide, the chloride process for producing titanium dioxide and titanium sponge has many advantages such as short process and green environmental protection, and the industrial capacity of the chloride process has developed rapidly. The contradiction of tight supply of titanium-rich materials for the chloride process titanium raw materials has become increasingly prominent. Titanium-rich materials mainly include high-titanium slag, natural rutile and artificial rutile. However, since my country's titanium resources are mainly co-existing resources of vanadium-titanium magnetite, the titanium concentrate obtained by beneficiation has low grade and high impurity content. The titanium-rich material prepared by reducing and melting with this titanium concentrate as raw material in an electric furnace still has high impurity content of calcium and magnesium, and the TiO2 grade can only reach 70-85%, which is difficult to meet the raw material quality requirements of the boiling chlorination method for titanium-rich materials. Most of them are produced by mixing with low-quality titanium concentrate and then using the sulfuric acid process.

[0004] In order to solve the problem of efficiently improving the quality of ilmenite concentrate to prepare titanium-rich material, CN107459058B discloses a method for producing artificial rutile from titanium concentrate, and obtains an artificial rutile-type titanium-rich material with a TiO2 content greater than 90% through mechanical activation, roasting treatment, magnetic separation, hot acid impurity removal, water washing and calcination; CN111676379A discloses a method for preparing a chlorinated titanium-rich material, which is modified by oxidative roasting after adding an alkali metal salt, and then selectively chlorinated to obtain a chlorinated titanium-rich material with a TiO2 content greater than 92%; CN108300875B discloses a method for preparing high-purity TiO2 by oxygen-enriched selective leaching of titanium concentrate, and high-purity TiO2 is obtained by high-pressure alkaline leaching of NaOH solution under oxygen-enriched conditions, acidic leaching of alkali decomposition products, hydrolysis, and high-temperature calcination. CN113088683B discloses a method for preparing low-temperature titanium chloride slag using low-grade titanium concentrate, using NH3-N2 and NH3-H2 as roasting gas, and effectively separating metallic iron and low-temperature titanium chloride slag through pre-oxidation, reduction nitridation, crushing ball milling, and magnetic separation.

[0005] To sum up, the current titanium concentrate has low grade and high impurity content, making it difficult to directly use the boiling chlorination production process. Titanium dioxide is mainly produced through the sulfuric acid method. The process of preparing titanium-rich materials using titanium concentrate as raw material through electric furnace reduction can produce higher-grade titanium slag, but the quality of the titanium slag is inconsistent and the impurity content is high, making it difficult to directly use it for the chlorination method to produce titanium dioxide and sponge titanium. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, which is used to solve one of the following technical problems: the impurity content of the titanium-rich material obtained by the existing process for preparing titanium-rich material is high; low-concentration acid leaching cannot achieve efficient leaching effect.

[0007] The above object of the present invention is achieved through the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, wherein a magnetic field is added during the acid leaching process.

[0009] Furthermore, the magnetic field is a pulsed magnetic field.

[0010] Furthermore, the pulse interval of the pulse magnetic field is 1 to 10 seconds, and the magnetic field intensity is 0.1 to 5T.

[0011] Furthermore, the method is carried out in an enhanced leaching device, which includes a reaction device and a reactor control device. The reaction device includes but is not limited to a reactor. The reactor is provided with a feed inlet and a discharge port. A thermal magnetic coupling device is provided outside the reactor. The thermal magnetic coupling device includes a heating component, an insulation layer and a magnetic field coil arranged in sequence. A thermocouple for measuring the temperature of the material is provided in the reactor body.

[0012] Furthermore, the reaction device also includes a magnetic stirrer, a stirring paddle, and a linkage shaft connecting the magnetic stirrer and the stirring paddle.

[0013] Furthermore, the reactor control device is connected to the thermal magnetic coupling device, the thermocouple and the magnetic agitator through connecting lines.

[0014] Furthermore, the method mainly comprises the following steps:

[0015] Step 1: Grind and sieve the ilmenite concentrate to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for more than 95%;

[0016] Step 2: Prepare a hydrochloric acid solution and fully mix the ilmenite concentrate with the hydrochloric acid solution;

[0017] Step 3: placing the mixed material obtained in step 2 into an enhanced leaching device with a magnetic field for leaching reaction;

[0018] Step 4: After the reaction is completed, the reaction material is cooled and filtered, and the filter cake is washed with water until it is neutral to obtain high-grade titanium slag and iron-containing leaching solution;

[0019] Step 5: Wash the titanium-containing slag with alkali, filter it after the reaction is completed, and wash the filter cake to neutrality to obtain high-quality artificial rutile; recover iron from the iron-containing leaching solution by spray pyrolysis.

[0020] Furthermore, in step 2, the concentration of the hydrochloric acid solution is 10% to 20%.

[0021] Furthermore, in step 2, the ratio of the hydrochloric acid solution to the concentrate is 7 mL: 1 g to 15 mL: 1 g.

[0022] Furthermore, in step 3, the reaction temperature is 110-170°C.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] 1) The method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate provided by the present invention utilizes the magnetism of the ilmenite concentrate itself and adopts a magnetic field to achieve the dissolution of the ilmenite concentrate under low acid concentration conditions, shorten the reaction time required for acid dissolution, and improve production efficiency.

[0025] 2) The method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate provided by the present invention adopts a pulsed magnetic field, which is an intermittent magnetic field and has a more significant effect on the disorder of the crystal structure in magnetic minerals. Therefore, based on the mechanism of the influence of the pulsed magnetic field on the crystal structure of magnetic minerals, it is beneficial to enhance the mineral dissolution activity, and can effectively enhance the leaching of ilmenite concentrate in a low-concentration sulfuric acid solution to obtain a higher leaching rate.

[0026] 3) The method provided by the present invention can achieve efficient leaching of elements such as titanium and iron under low acid concentration conditions by accurately controlling process parameters such as magnetic field intensity, stirring speed, temperature, acidity, etc., with high efficiency and good leaching effect, and is suitable for large-scale application.

[0027] Other features and advantages of the present invention will be described in the following embodiments, and some of them can be obtained from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are only for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. The same reference symbols denote the same contents throughout the accompanying drawings.

[0029] Figure 1 is a process flow chart of the method of the present invention;

[0030] Figure 2 It is a schematic diagram of the structure of the enhanced leaching device;

[0031] Figure 3 Schematic diagram of the cross section of the thermal magnetic coupling device.

[0032] Reference numerals:

[0033] 1-1-reactor control device; 1-2-reactor; 1-3-thermal magnetic coupling device; 1-4-feeding port; 1-5-linkage shaft; 1-6-connecting piece; 1-7-stirring paddle; 1-8-discharging port; 1-9-connecting line; 1-10-magnetic stirrer; 1-11-thermocouple; 1-3-1-heating component; 1-3-2-insulation layer; 1-3-3-magnetic field coil. DETAILED DESCRIPTION

[0034] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.

[0035] The present invention provides a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, which mainly comprises the following steps:

[0036] Step 1: Grind and sieve the ilmenite concentrate to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for more than 95%;

[0037] Step 2: Prepare a hydrochloric acid solution and fully mix the ilmenite concentrate with the hydrochloric acid solution;

[0038] Step 3: placing the mixed material obtained in step 2 into an enhanced leaching device with a magnetic field for leaching reaction;

[0039] Step 4: After the reaction is completed, the reaction material is cooled and filtered, and the filter cake is washed with water until it is neutral to obtain high-grade titanium slag and iron-containing leaching solution;

[0040] Step 5: Wash the titanium-containing slag with alkali, filter it after the reaction is completed, and wash the filter cake to neutrality to obtain high-quality artificial rutile; recover iron from the iron-containing leaching solution by spray pyrolysis.

[0041] Specifically, in the above step 1, the ilmenite concentrate is a magnetic mineral, and the ilmenite concentrate mainly contains valuable metal elements such as iron and titanium, among which TiO2>40wt%.

[0042] Specifically, in step 2, the hydrochloric acid concentration is too low, and the leaching reaction is incomplete; a high hydrochloric acid concentration can easily lead to incomplete hydrolysis and precipitation of the dissolved titanium during the leaching process, and corrode the reaction container, and subsequently produce a large amount of high-concentration waste acid solution, resulting in high production costs; therefore, taking all factors into consideration, the concentration of the hydrochloric acid solution is controlled to be 10% to 20%, and exemplary concentrations are 13%, 15%, and 18%.

[0043] Specifically, in step 2, when the ratio of hydrochloric acid solution to concentrate is too large, the processing volume is limited and the acid reaction is incomplete; when the ratio of hydrochloric acid solution to concentrate is small, it is difficult to mix the reaction materials and the reaction efficiency is low; therefore, taking all factors into consideration, the ratio of hydrochloric acid solution to concentrate is controlled to be (7mL:1g) to (15mL:1g). Exemplarily, the ratio of hydrochloric acid solution to concentrate is 7mL:1g, 10mL:1g, and 12mL:1g.

[0044] Specifically, in step 3, for magnetic minerals, the effects of magnetic elements and non-magnetic elements in the mineral lattice on the magnetic field are somewhat different. The magnetic field can change the vibration and orientation of magnetic ions in the magnetic minerals, produce vacancy defects in the mineral structure, and change the entropy value of the material at the molecular level, thereby effectively enhancing the leaching effect of magnetic minerals in low-concentration hydrochloric acid solutions.

[0045] Considering that the interaction between the pulsed magnetic field and the mineral is intermittent, a resonance-like effect can be achieved by adjusting the magnetic field pulse frequency, resulting in more mineral lattice defects and improving leaching activity. Therefore, the magnetic field in step 3 uses a pulsed magnetic field.

[0046] Specifically, in step 3, the pulsed magnetic field is generated by an electromagnetic coil.

[0047] It should be noted that if the intensity of the pulsed magnetic field is too small, the enhanced leaching effect will not be obvious. If the intensity of the magnetic field is too large, the leaching effect will be limited, but the equipment manufacturing cost will increase exponentially. If the pulse time interval is too small or too large, it is difficult to enhance the leaching process of magnetic minerals, and a certain degree of matching with the magnetic substances in the minerals is required. Therefore, taking comprehensive considerations, the pulse interval is controlled to be 1 to 10 seconds and the magnetic field intensity is controlled to be 0.1 to 5T.

[0048] Specifically, in the above step 3, when the magnetic field intensity is 0.1 to <1 T, the pulse interval is 1 to 3 s.

[0049] Specifically, in the above step 3, when the magnetic field strength is 1-2T, the pulse interval is 3-7s (for example, 3-5s), and when the magnetic field strength is greater than 2-5T, the pulse interval is 4-10s (for example, 4-7s).

[0050] Specifically, in step 3, stirring is performed during the leaching process. Considering that the degree of thermal motion of atoms and electrons in various mineral substances is different under different temperature conditions, the leaching activity also has certain differences. Under magnetic field conditions, the temperature and magnetic field have a certain degree of matching to achieve a better enhanced leaching effect; the reaction time is short, the leaching is incomplete, and when a certain reaction time is reached, the reaction is basically complete. Continuing to extend the reaction time cannot significantly increase the leaching rate; stirring mainly provides a certain centrifugal force and shear force, so that the mineral particles and the liquid leaching agent have a good mixing effect, and reduce the surface diffusion layer of the mineral particles. When the stirring speed is too small, it is easy to cause the sedimentation of the mineral particles. When the stirring speed is too large, the mineral particles and the liquid leachate are easy to form a rotation without relative motion, and the mixing effect cannot be achieved; in addition, the pulsed magnetic field also has a certain stirring effect on magnetic minerals. The mechanical stirring effect needs to cooperate with the pulsed magnetic field stirring effect to achieve a better enhanced leaching effect. Comprehensively considered, in the control step 3, the reaction temperature is 110-170°C, the reaction time is 0.5-2 hours, and the speed provided by the stirring is 200-700r / min. Exemplarily, the reaction temperature is 120°C, 130°C, 140°C, 150°C, 160°C; the reaction time is 1 hour, 1.5 hours, 2 hours; and the stirring speed is 300 r / min, 400 r / min, 500 r / min, 600 r / min.

[0051] Specifically, in step 3, the stirring is swirl stirring or impeller stirring.

[0052] In the present invention, the process parameters of each step are precisely controlled, so that the concentration of the used hydrochloric acid is low, the safety is good, the leaching time is short and the efficiency is high.

[0053] Specifically, the filtration in step 4 is a conventional liquid-solid separation method, including but not limited to filter press.

[0054] Specifically, in the above step 5, considering that the concentration of the alkaline solution used in the alkali washing is low, the impurity removal effect is not obvious, and if the concentration of the alkaline solution is too high, the production cost is high and it is easy to cause the dissolution loss of some TiO2; the increase in the temperature of the solution in the alkali washing helps to improve the reaction efficiency of the alkali leaching process, and the high temperature does not significantly improve the reaction efficiency but increases energy consumption; the reaction time is short, the impurity removal is not thorough, the rutile product grade is low, and the reaction time is too long, the production cycle is long and the production efficiency is low. Therefore, the alkaline solution is controlled to be NaOH, and the concentration of the alkaline solution is 1.0-3.0 mol / L.

[0055] Specifically, in the above step 5, alkaline washing is carried out under normal pressure and a solution temperature of 50 to 95°C, and the reaction is carried out for 0.5 to 2 hours; illustratively, the concentration of the alkaline solution is 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, the solution temperature is 60°C, 70°C, 80°C, 90°C, and the reaction time is 1 hour, 1.5 hours, or 2 hours.

[0056] Specifically, in the above step 5, if the temperature of the spray pyrolysis is too low, the reaction will be incomplete, and if the temperature is high, the energy consumption will be high; if the time is short, the reaction will be incomplete, and if the time is too long, the production efficiency will be affected; if the spray pressure is small, the injection speed will be slow and the production efficiency will be low, and if the spray pressure is too high, it will cause incomplete pyrolysis. Therefore, the temperature of the mist pyrolysis is controlled to be 700-800°C, the time is 20-60min, and the spray pressure is 0.1-0.5Mpa. Exemplarily, the temperature is 720°C, 750°C, 780°C, the time is 30min, 40min, 50min, and the spray pressure is 0.2Mpa, 0.3Mpa, 0.4Mpa.

[0057] Specifically, in the above step 5, the grade of high-quality artificial rutile reaches more than 85%.

[0058] like Figure 2 As shown, the present invention also provides an enhanced leaching device for implementing the above method, and the enhanced leaching device includes a reaction device and a reactor control device 1-1.

[0059] Specifically, the above-mentioned reaction device includes but is not limited to a reactor 1-2, the reactor 1-2 is provided with a feed port 1-4 and a discharge port 1-8, a thermal magnetic coupling device 1-3 is provided outside the reactor 1-2, the thermal magnetic coupling device 1-3 includes a heating component 1-3-1, an insulation layer 1-3-2 and a magnetic field coil 1-3-3 which are arranged in sequence, and a thermocouple 1-11 for measuring the temperature of the material is provided in the reactor body of the reactor 1-2.

[0060] Considering that the magnetic field coil 1-3-3 can generate heat while generating a magnetic field, coupling the heating component 1-3-1 with the magnetic field coil 1-3-3 can maximize the use of heat.

[0061] Specifically, the above-mentioned reaction device also includes a magnetic stirrer 1-10, a stirring paddle 1-7, and a linkage shaft 1-5 connecting the magnetic stirrer 1-10 and the stirring paddle 1-7.

[0062] Specifically, the reactor control device 1-1 is connected to the thermal magnetic coupling device 1-3, the thermocouple 1-11 and the magnetic agitator 1-10 through the connecting line 1-9. The reactor control device 1-1 controls the magnetic field intensity, pulse interval and reaction material temperature during the reaction process.

[0063] Specifically, the reaction kettle is made of Hastelloy acid corrosion resistant material or stainless steel with polytetrafluoroethylene lining.

[0064] In the hydrochloric acid leaching process of the existing ilmenite concentrate, the leaching effect is poor when the hydrochloric acid concentration is low, and concentrated hydrochloric acid needs to be used for leaching, which is easy to produce a large amount of high-concentration waste acid. The method of the present invention takes into account that the magnetic field has a certain influence on the thermal motion of atoms and electrons in the material. When the magnetic field is strong enough, it can have a certain influence on the thermodynamics and kinetics of the chemical reaction between the substances. When the magnetic field is weak, the effect is weak and can be ignored. However, for magnetic minerals, there are certain differences between the effects of magnetic elements and non-magnetic elements in the mineral lattice and the magnetic field. The magnetic field can produce vacancy defects in the mineral structure and change the material entropy value from the molecular level by changing the vibration and orientation of magnetic ions in the magnetic mineral, and the pulsed magnetic field is an intermittent magnetic field, which has a more significant effect on the disorder of the crystal structure in the magnetic mineral. Therefore, based on the influence mechanism of the pulsed magnetic field on the crystal structure of magnetic minerals, it is beneficial to enhance the mineral dissolution activity, and can effectively strengthen the leaching of ilmenite in a low-concentration hydrochloric acid solution to obtain a higher leaching rate.

[0065] The method of the invention utilizes the magnetism of ilmenite itself and adopts a magnetic field to realize the dissolution of ilmenite under the condition of low acid concentration, shortens the reaction time required for acid dissolution, and improves production efficiency.

[0066] Example 1

[0067] like Figure 2 As shown, this embodiment provides an enhanced leaching device, which includes a reaction device and a reactor control device 1-1.

[0068] Specifically, the reaction device includes a reactor 1-2, which is provided with a feed port 1-4 and a discharge port 1-8. A thermal magnetic coupling device 1-3 is provided outside the reactor 1-2. The thermal magnetic coupling device 1-3 includes a heating component 1-3-1, an insulation layer 1-3-2 and a magnetic field coil 1-3-3 which are arranged in sequence. A thermocouple 1-11 for measuring the temperature of the material is provided in the reactor body of the reactor 1-2.

[0069] Specifically, the above-mentioned reaction device also includes a magnetic stirrer 1-10, a stirring paddle 1-7, and a linkage shaft 1-5 connecting the magnetic stirrer 1-10 and the stirring paddle 1-7.

[0070] Specifically, the reactor control device 1-1 is connected to the thermal magnetic coupling device 1-3, the thermocouple 1-11 and the magnetic couple stirrer 1-10 through the connecting line 1-9.

[0071] Specifically, the reaction kettle is made of stainless steel with a polytetrafluoroethylene lining.

[0072] Example 2

[0073] This embodiment provides a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, using the device of embodiment 1, comprising the following steps:

[0074] The ilmenite concentrate was ground and sieved to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for 95%; the ilmenite concentrate was fully mixed with 13%, 15%, and 18% hydrochloric acid solutions, the ratio of ilmenite concentrate to hydrochloric acid solution was 1g:7mL, and after uniform mixing, it was put into a reaction device, and the magnetic field strength was set to 1T and the pulse interval was 3s. The reaction was carried out at 150°C and a stirring speed of 500r / min for 1 hour; after the leaching reaction was completed, the reaction materials were cooled and filtered to obtain a filter cake (titanium-containing slag) and an iron-containing solution, and the filter cake was washed with industrial water to neutrality; the titanium-containing slag was alkaline-washed with a 2.0mol / L NaOH solution at 70°C for 1 hour. After the reaction was completed, it was filtered and the filter cake was washed to neutrality to obtain a high-quality artificial rutile product; the iron-containing leachate was spray-pyrolyzed at 700°C and a spray pressure of 0.3Mpa for 40 minutes to obtain an iron red product. The results of titanium / iron leaching rate, artificial rutile TiO2 grade, titanium recovery rate, iron recovery rate, and iron red product Fe2O3 grade during the leaching process are shown in Table 1. It should be noted that since the dissolved titanium component is hydrolyzed into the acid leaching residue during the leaching process, the titanium leaching rate is relatively low. The process indicators of titanium mainly include artificial rutile grade and titanium recovery rate as the main reference indicators. With the increase of hydrochloric acid concentration, the iron leaching rate increases, the artificial rutile grade improves, and the titanium recovery rate remains basically unchanged. It shows that within this range, the efficient dissolution of ilmenite concentrate and the effective separation of titanium and iron components in the solution can be effectively achieved to obtain high-quality artificial rutile.

[0075] The grade of artificial rutile in this embodiment reaches more than 91%, for example, 91.2% to 94%; the titanium recovery rate reaches more than 94%, for example, 94.3% to 96%; and the iron recovery rate reaches more than 82%, for example, 82.5% to 93%.

[0076] Table 1 Results of each process under different hydrochloric acid concentration conditions

[0077]

[0078] Example 3

[0079] This embodiment provides a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, using the device of embodiment 1, comprising the following steps:

[0080] The ilmenite concentrate was ground and sieved to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for 95% of the total; the ilmenite concentrate was fully mixed with a 15% hydrochloric acid solution, the ratio of the ilmenite concentrate to the hydrochloric acid solution was 1g:15mL, and after being evenly mixed, it was put into a reaction device, and different magnetic field strengths and pulse intervals were set, and the reaction was carried out at 150°C and a stirring speed of 500r / min for 0.5 hours; after the leaching reaction was completed, the reaction materials were cooled and filtered to obtain a filter cake (titanium-containing slag) and an iron-containing solution, and the filter cake was washed with industrial water to neutrality; the titanium-containing slag was alkaline washed with a 3.0mol / L NaOH solution at 95°C for 2 hours, and after the reaction was completed, it was filtered and the filter cake was washed to neutrality to obtain a high-quality artificial rutile product; the iron-containing leachate was spray-pyrolyzed at 800°C and a spray pressure of 0.5Mpa for 60 minutes to obtain an iron red product. The results of titanium / iron leaching rate, artificial rutile TiO2 grade, titanium recovery rate, iron recovery rate, and iron red product Fe2O3 grade during the leaching process are shown in Table 2. The magnetic field intensity and pulse interval have a great influence on the leaching process, titanium and iron recovery rates and product quality, but they are not positively correlated with the magnetic field intensity and pulse interval. Instead, the magnetic field intensity and pulse interval need to have a certain degree of matching to significantly improve the leaching effect.

[0081] The grade of artificial rutile in this embodiment reaches more than 79%. In some preferred embodiments, the grade of artificial rutile reaches more than 85%, for example, 85.5% to 94%; the titanium recovery rate reaches more than 89%, for example, 89% to 97%; the iron recovery rate reaches more than 80%, for example, 80% to 96%.

[0082] Table 2 Results of each process under different magnetic field strength and pulse interval conditions

[0083]

[0084]

[0085] Example 4

[0086] This embodiment provides a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, using the device of embodiment 1, comprising the following steps:

[0087] The ilmenite concentrate was ground and sieved to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for 95% of the total; the ilmenite concentrate was fully mixed with a 15% hydrochloric acid solution, the ratio of the ilmenite concentrate to the hydrochloric acid solution was 1g:10mL, and after being evenly mixed, it was put into a reaction device, and different magnetic field strengths and different temperatures were set, and the reaction was carried out for 2 hours under the conditions of a pulse interval of 3s and a stirring speed of 500r / min; after the leaching reaction was completed, the reaction materials were cooled and filtered to obtain a filter cake (titanium-containing slag) and an iron-containing solution, and the filter cake was washed with industrial water to neutrality; the titanium-containing slag was alkaline washed with a 1.0mol / L NaOH solution at 50°C for 0.5 hours. After the reaction was completed, it was filtered and the filter cake was washed to neutrality to obtain a high-quality artificial rutile product; the iron-containing leachate was spray-pyrolyzed at 800°C and a spray pressure of 0.1Mpa for 20 minutes to obtain an iron red product. The results of titanium / iron leaching rate, artificial rutile TiO2 grade, titanium recovery rate, iron recovery rate, and iron red product Fe2O3 grade during the leaching process are shown in Table 3. The reaction effect is not a positively correlated increase with the increase of magnetic field intensity and reaction temperature, but the magnetic field and temperature have a certain matching mechanism for the reaction effect.

[0088] The grade of artificial rutile in this embodiment reaches more than 85%, for example, 85% to 95%; the titanium recovery rate reaches more than 90%, for example, 90% to 97%; and the iron recovery rate reaches more than 76%, for example, 76.3% to 97%.

[0089] Table 3 Results of each process under different magnetic field strength and reaction temperature conditions

[0090]

[0091] Example 5

[0092] This embodiment provides a method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, using the device of embodiment 1, comprising the following steps:

[0093] The ilmenite concentrate is ground and sieved to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for 95% of the total; the ilmenite concentrate is fully mixed with a 15% hydrochloric acid solution, the ratio of the ilmenite concentrate to the hydrochloric acid solution is 1g:10mL, and after mixing evenly, it is placed in a reaction device, and different stirring speeds are set. The reaction is carried out at a magnetic field intensity of 2T, a pulse interval of 3s, and 150°C for 2 hours; after the leaching reaction is completed, the reaction material is cooled and filtered to obtain a filter cake (titanium-containing slag) and an iron-containing solution, and the filter cake is washed with industrial water to neutrality; the titanium-containing slag is alkaline washed with a 1.0 mol / L NaOH solution at 50°C for 0.5 hours. After the reaction is completed, it is filtered and the filter cake is washed to neutrality to obtain a high-quality artificial rutile product; the iron-containing leachate is spray-pyrolyzed at 800°C and a spray pressure of 0.1Mpa for 20 minutes to obtain an iron red product. The results of titanium / iron leaching rate, artificial rutile TiO2 grade, titanium recovery rate, iron recovery rate, and red iron product Fe2O3 grade during the leaching process are shown in Table 4. By adjusting the stirring speed, the leaching effect is improved compared with that in Example 3, indicating that stirring has a certain degree of adaptability with the magnetic field intensity and the pulse interval.

[0094] Table 4 Results of each process under different stirring speed conditions

[0095]

[0096] The inventor has conducted a large number of experimental studies during the research process, and now uses some solutions with poor effects as comparative examples.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing artificial rutile by acid leaching of ilmenite concentrate, comprising the following steps:

[0099] The ilmenite concentrate is ground and sieved to obtain an ilmenite concentrate with a particle size of less than 74 microns, accounting for 95%; the ilmenite concentrate is fully mixed with a 15% hydrochloric acid solution, the ratio of the ilmenite concentrate to the hydrochloric acid solution is 1g:10mL, and after mixing evenly, it is placed in a reaction device, different temperatures are set, and the reaction is carried out for 2 hours under the conditions of no magnetic field and a stirring speed of 500r / min; after the leaching reaction is completed, the reaction materials are cooled and filtered to obtain a filter cake (titanium-containing slag) and an iron-containing solution, and the filter cake is washed with industrial water to neutrality; the titanium-containing slag is alkaline washed with a 1.0mol / L NaOH solution at 50°C for 0.5 hours. After the reaction is completed, it is filtered and the filter cake is washed to neutrality to obtain a high-quality artificial rutile product; the iron-containing leachate is spray-pyrolyzed at 800°C and a spray pressure of 0.1Mpa for 20 minutes to obtain an iron red product. The results of titanium / iron leaching rate, artificial rutile TiO2 grade, titanium recovery rate, iron recovery rate, and iron red product Fe2O3 grade during the leaching process are shown in Table 5.

[0100] Table 5 Results of each process under different reaction temperatures and no magnetic field conditions

[0101]

[0102]

[0103] By comparing Example 4 with Comparative Example 1, it can be seen that under the action of the pulsed magnetic field, the leaching effect of ilmenite concentrate is significantly enhanced; under the action of the magnetic field, the effects of reaction temperature and stirring speed on the leaching effect are not positively correlated, but have a certain matching system; under the condition of no magnetic field, the higher the reaction temperature, the better the iron leaching effect, with a certain optimal range. It should be noted that with the increase of reaction temperature, the decrease in titanium leaching rate under the condition of no magnetic field is caused by the hydrolysis of the leached titanium component when the temperature is high.

[0104] Comparative Example 2

[0105] This comparative example provides a method for preparing artificial rutile by acid leaching of ilmenite concentrate. The method is basically the same as the steps of Example 4, except that the magnetic field intensity is 5 T and the pulse interval is 30 s.

[0106] In this comparative example, the titanium leaching rate is 15.38%, the iron leaching rate is 94.21%, the artificial rutile grade is 92.18%, the titanium recovery rate is 77.31%, the iron red product is 88.75%, and the iron recovery rate is 92.18%. The main difference is that more titanium enters the solution during the leaching process, and the hydrolysis is incomplete, so that more titanium components remain in the solution, resulting in a high leaching rate and a low titanium recovery rate.

[0107] Comparative Example 3

[0108] This comparative example provides a method for preparing artificial rutile by acid leaching of ilmenite concentrate, which is the same as Example 3, except that: hydrochloric acid solutions with concentrations of 20%, 24%, and 30% are used respectively, and leaching is carried out under the conditions of a magnetic field strength of 2T and a pulse interval of 3s, and the results are shown in Table 6. By comparison, it is found that under magnetic field conditions, the iron leaching rate, iron red grade, and iron recovery rate are basically unchanged when hydrochloric acid with higher acidity is used for leaching; when the hydrochloric acid concentration is 20%, there is not much difference compared with Example 3, but when the acid concentration is higher, the titanium component in the leachate cannot be completely hydrolyzed, resulting in a high residual titanium concentration in the leachate (manifested as a high leaching rate), which ultimately leads to a decrease in the titanium recovery rate. It shows that under the action of the magnetic field, the acidity is appropriately increased, and the leaching effect has no gain effect, and excessive acidity will lead to the negative impact of low recovery rate.

[0109] Table 6 Results of each process under different hydrochloric acid concentration conditions

[0110]

[0111] Comparative Example 4

[0112] This comparative example provides a method for preparing artificial rutile by acid leaching of ilmenite concentrate. Compared with Example 4, the method is basically the same, except that: this comparative example is a reaction process using 30% hydrochloric acid solution at 150°C under the condition of no magnetic field, and the results are 15.12% titanium leaching rate, 96.78 iron leaching rate, 91.67% artificial rutile grade, 80.13% titanium recovery rate, 85.12% iron red grade, and 94.38% iron recovery rate. Comparison (Comparative Example 3) found that with or without a magnetic field, high-concentration acid leaching process, when there is a magnetic field, can promote the hydrolysis of titanium, reduce the participation of titanium in the solution (reflected in the lower leaching rate), and improve the recovery rate of titanium; compared with Example 4, it is found that the reaction effect of high-concentration acid under the condition of no magnetic field is basically the same as the reaction effect of low-concentration acid under the condition of magnetic field.

[0113] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing artificial rutile by enhanced acid leaching of ilmenite concentrate, characterized in that: The method adds a magnetic field during the acid leaching process.

2. The method according to claim 1, characterized in that The magnetic field is a pulsed magnetic field.

3. The method according to claim 2, characterized in that The pulse interval of the pulse magnetic field is 1 to 10 seconds, and the magnetic field intensity is 0.1 to 5T.

4. The method according to claim 1, characterized in that: The method is carried out in an enhanced leaching device, which comprises a reaction device and a reactor control device (1-1), wherein the reaction device includes but is not limited to a reactor (1-2), wherein the reactor (1-2) is provided with a feed port (1-4) and a discharge port (1-8), wherein a thermal magnetic coupling device (1-3) is provided outside the reactor (1-2), wherein the thermal magnetic coupling device (1-3) comprises a heating component (1-3-1), a thermal insulation layer (1-3-2) and a magnetic field coil (1-3-3) which are arranged in sequence, and wherein a thermocouple (1-11) for measuring the temperature of the material is provided inside the reactor body of the reactor (1-2).

5. The method according to claim 4, characterized in that The reaction device also includes a magnetic stirrer (1-10), a stirring paddle (1-7), and a linkage shaft (1-5) connecting the magnetic stirrer (1-10) and the stirring paddle (1-7).

6. The method according to claim 5, characterized in that The reactor control device (1-1) is connected to the thermal magnetic coupling device (1-3), the thermocouple (1-11) and the magnetic couple stirrer (1-10) via a connecting line (1-9).

7. The method according to claim 1, characterized in that The method mainly comprises the following steps: Step 1: Grind and sieve the ilmenite concentrate to obtain ilmenite concentrate with a particle size of less than 74 microns, accounting for more than 95%; Step 2: Prepare a hydrochloric acid solution and fully mix the ilmenite concentrate with the hydrochloric acid solution; Step 3: placing the mixed material obtained in step 2 into an enhanced leaching device with a magnetic field for leaching reaction; Step 4: After the reaction is completed, the reaction material is cooled and filtered, and the filter cake is washed with water until it is neutral to obtain high-grade titanium slag and iron-containing leaching solution; Step 5: Wash the titanium-containing slag with alkali, filter it after the reaction is completed, and wash the filter cake to neutrality to obtain high-quality artificial rutile; recover iron from the iron-containing leaching solution by spray pyrolysis.

8. The method according to claim 7, characterized in that In step 2, the concentration of the hydrochloric acid solution is 10% to 20%.

9. The method according to claim 7, characterized in that: In the step 2, the ratio of the hydrochloric acid solution to the concentrate is 7 mL: 1 g to 15 mL: 1 g.

10. The method according to any one of claims 7 to 9, characterized in that: In the step 3, the reaction temperature is 110-170°C.

Citation Information

Patent Citations

  • A method for producing synthetic rutile from titanium concentrate

    CN107459058B

  • A method for preparing high-purity TiO2 by selective leaching of titanium concentrate with oxygen enrichment

    CN108300875B

  • Method for preparing chlorinated titanium-rich material through Panxi titanium concentrate

    CN111676379A

  • A method for preparing low-temperature titanium chloride slag from low-grade titanium concentrate

    CN113088683B

Cited By

  • Method for preparing artificial rutile from ilmenite concentrate and application of pulsed magnetic field in method

    CN121800216A

  • A method for preparing synthetic rutile from ilmenite concentrate and the application of pulsed magnetic fields in the process.

    CN121800216B